2019
DOI: 10.1109/access.2019.2917316
|View full text |Cite
|
Sign up to set email alerts
|

Trim Strategy, Control Model, and Flight Dynamics Characteristics of Canard Rotor/Wing Aircraft in Transition Mode

Abstract: The transition mode of canard rotor/wing (CRW) aircraft is complex and important. During the transition flight, components that generate lift are transferred from one to another, in addition, the redundancy of control system may induce control conflict even plane crash if they don't cooperate well. It is significant to investigate the trim strategy, redundant control, and flight dynamics characteristics of CRW during transition flight. First, aerodynamic forces and moments were calculated by combining the blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The author has constructed the nonlinear flight dynamics model of SR aircraft in transitional mode (Gao et al , 2019), as shown in equations (1) and (2): where m is the aircraft mass, u , v and W are the components of the flight velocity on the x , y and z axes of the body axis system, q , p and r are the pitch rate, roll rate and yaw rate, respectively, and I x , I y and I z are the moments of inertia. I xz is the product of inertia.…”
Section: Design Of Manipulation Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…The author has constructed the nonlinear flight dynamics model of SR aircraft in transitional mode (Gao et al , 2019), as shown in equations (1) and (2): where m is the aircraft mass, u , v and W are the components of the flight velocity on the x , y and z axes of the body axis system, q , p and r are the pitch rate, roll rate and yaw rate, respectively, and I x , I y and I z are the moments of inertia. I xz is the product of inertia.…”
Section: Design Of Manipulation Modelmentioning
confidence: 99%
“…M x , M y and M z are the resultant moments of the x , y and z axes. The calculation of specific aerodynamic force and torque can refer to Gao (2019).…”
Section: Design Of Manipulation Modelmentioning
confidence: 99%
See 3 more Smart Citations